Antibiotic-dependent effect of probiotics in patients with non-small cell lung cancer treated with PD-1 checkpoint blockade. (September 2022) - Takada, Kazuki; Buti, Sebastiano; Bersanelli, Melissa; Shimokawa, Mototsugu; Takamori, Shinkichi; Matsubara, Taichi; Takenaka, Tomoyoshi; Okamoto, Tatsuro; Hamatake, Motoharu; Tsuchiya-Kawano, Yuko; Otsubo, Kohei; Nakanishi, Yoichi; et al.
Abstract: Background: We previously validated in European patients with NSCLC treated with programmed death-1 (PD-1) checkpoint inhibitors the cumulative detrimental effect of concomitant medications. Materials and methods: We evaluated the prognostic ability of a "drug score" computed on the basis of baseline corticosteroids, proton pump inhibitors, and antibiotics, in an independent cohort of Japanese patients with advanced NSCLC treated with PD-1 monotherapy. Subsequently, we assessed the impact of baseline probiotics on the score's diagnostic ability and their interaction with antibiotics in influencing survival. Results: Among the 293 eligible patients, good (19.5 months), intermediate (13.4 months), and poor (3.7 months) risk groups displayed a significantly different overall survival (OS) (log-rank test for trend: p = 0.016), but with a limited diagnostic ability (C-index: 0.57, 95%CI: 0.53–0.61), while no significant impact on progression-free survival (PFS) was reported (log-rank test for trend: p = 0.080; C-index: 0.55, 95%CI: 0.52–0.58). Considering the impact of the probiotics∗antibiotics interaction (p-value 0.0510) on OS, we implemented the drug score by assigning 0 points to concomitant antibiotics and probiotics. With the adapted drug score good, intermediate, and poor risk patients achieved a median OS of 19.6 months, 13.1 months, and 3.7 months, respectively, with a similar diagnostic ability (log-rank test for trend: p = 0.006; C-index: 0.58, 95%CI: 0.54–0.61). However, the diagnostic ability for PFS of the adapted score was improved (log-rank test for trend: p = 0.034; C-index: 0.62, 95%CI: 0.54–0.69). Conclusions: Although we failed to validate the drug score in this independent Japanese cohort, we showed that probiotics may have an antibiotic-dependent impact on its prognostic value. Further investigation looking at the effect of concomitant medications and probiotics across cohorts of different ethnicities is warranted. Highlights: Concomitant medications affect clinical outcomes from immune checkpoint inhibitors. We previously validated a prognostic drug score in European patients with NSCLC. We explored the prognostic ability of the drug score in Japanese patients with NSCLC. The use of probiotics might mitigate the deleterious effect of antibiotics. Racial differences should be considered when investigating this topic.